Consultancy In Action: Implementing The ICF-CY Within The New Practices In Special Education Needs Assessment In Armenia - Sanches-Ferreira, Manuela (2018)
Over the last decade, with the help of UNICEF, international organizations and the civil society, the Armenian government has been developing efforts to reform the education system and promote inclusive education by expanding the network of inclusive schools and increasing budgetary allocations to children with special education needs. As a next major step the Ministry of Education plans to gradually transform special schools into resources centres supporting inclusive education.